Influence analysis of energy policies on comprehensive performance of CCHP system in different buildings - Kang, Ligai; Wu, Xiaojing; Yuan, Xiaoxue; Ma, Kunru; Wang, Yongzhen; Zhao, Jun; An, Qingsong (Energy (Oxford), 2021)
As an on-site energy supply system, combined cooling, heating and power (CCHP) system plays significant role. Thus, CCHP systems servicing four types of buildings were employed in this paper. Considering high initial investment and off-design operation, a multi-objective optimization model and a bi-level programming method integrated with operation and design were proposed. Nominal capacity configurations were optimized with no supportive policy. Then influence of capital subsidy and feed-in tariff policies to system comprehensive performance were illustrated. Results show that CCHP system servicing residential building could not achieve economic merits whatever energy policy was employed. CCHP system servicing hotel and hospital could realize better comprehensive performance than that of office. While the capacity of power generation unit was lower than 1.5 MW and capital subsidy was lower than 3000 ¥/kW, the capital subsidy policy had slight effect on system performance. For feed-in tariff policy, when feed-in tariff ratio (Esale/Egrid) was quite low, nearly no change on system performance would be obtained. And when the feed-in tariff ratio was relatively high, the energy and environment performance would decrease significantly. If feed-in tariff ratio was in a reasonable price range, this policy would have a positive effect on CCHP system with different building types. •A bi-level programming method integrated with operation and design was proposed.•Comprehensive performance obtained by AHP is employed as the optimization objective.•The analysis is performed on energy system in different four types of buildings.•Performances are presented and compared under different energy policies.